Analisis Human Resources Competence (HRC) Dalam Perspektif Human Resources Scorecard (HRSC) Pada Badan Penyelenggara Jaminan Produk Halal - Prasetyo, Mohammad Ferri Adi; Martini, Nelly (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to analyze the dimensions of Human Resource Competence (HR Competence) within the framework of the Badan Penyelenggara Jaminan Produk Halal. This research employs a combination of primary and secondary data. The data collection method involves distributing closed questionnaires to respondents. The collected data is analyzed using a mixed approach that combines qualitative and quantitative methods. The results of this study indicate that the management of Human Resources, when evaluated from the perspective of HR Competence, has achieved a satisfactory level of optimization. However, there is room for improvement in the HR management system. Contributing factors to this situation include a deficiency in the objective performance assessment system within the Badan Penyelenggara Jaminan Produk Halal. Additionally, there are still team members in the Human Resources department who do not meet the competency standards in formulating performance indicators. Furthermore, the educational backgrounds of some employees are not fully aligned with their tasks and responsibilities, which also contributes to this situation